EXPLORING MORAL DEVELOPMENT AND ETHICAL UNDERSTANDING IN CHILDREN WITH LEARNING DISABILITIES: A STUDY OF TEACHING ETHICS AND AKHLAQ IN SPECIAL NEEDS EDUCATION - Usman Jaffer; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Nur Hidayati Mohd Darwis; Nur Syaqirah Natasha Mohamad Yusaini; Siti Sarah Rusli; Siti Zulaikha Zul Alam; Muhammad Afiq Ikmal Yusof; Ilham Syahmi Shahrul, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study investigates the moral development and comprehension of ethics and akhlaq (moral virtues) in children with learning disabilities, particularly focusing on the influence of educational practices and environmental interactions. Utilizing a sample of 15 primary schoolers from Sekolah Kebangsaan Pendidikan Khas Kuantan, aged 8 to 12 years, with disorders like autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and dyslexia, the study employs the Piagetian method, children evaluation, and teacher assessments to explore ethical understanding and behavior. The research integrates principles from Islamic teachings, Western ethics, and developmental psychology, particularly drawing on theories from Piaget, Vygotsky, Gardner, and Bandura. Findings reveal nuanced moral perceptions among the children, with their judgments in given scenarios reflecting a combination of autonomous morality and the age-related cognitive shift in understanding actions based on intentions and consequences. The study also highlights the effectiveness of creative and adaptive teaching methods, including psychomotor activities, in enhancing moral understanding in children with learning disabilities. Teacher evaluations indicate the impact of school curriculum and individualized teaching methods on instilling ethical values. Despite its limited sample size and challenges in maintaining a controlled environment, the study provides valuable insights into the moral development of children with learning difficulties, suggesting the need for tailored educational strategies and community involvement in moral education. This research contributes to a deeper understanding of ethical development in special needs education and underscores the importance of considering cognitive, social, and environmental factors in teaching ethics and akhlaq to children with learning disabilities.